Flow in Games (and Everything Else). - Chen, Jenova (Communications of the ACM, 2007)
The article discusses the concept of "flow" in games and other computer software. Flow represents the feeling of complete and energized focus in an activity, characterized by a high level of enjoyment and fulfillment. The eight major components of Flow, which include a challenging activity requiring skill, a merging of action and awareness, clear goals, direct and immediate feedback, concentration on the task at hand, a sense of control, a loss of self consciousness, and an altered sense of time, are analyzed.